Development of Cerbon Children's Storybook (BCAC) as a Literacy Learning Media for Early Childhood in Cirebon - Carilah, Ilah; Priyanti, Nita (Kirana Publisher (KNPub), 2025)
This study aims to develop Buku Cerita Anak Cerbon (BCAC) as a reading literacy learning media for early childhood, using the 4D development model which consists of four stages: Define, Design, Develop, and Disseminate. In the Define stage, interviews were conducted with the head of the kindergarten and teachers as well as observations of learners to analyse needs and identify children's early literacy skills. The Design stage involved designing the BCAC by incorporating elements of Cirebon culture, such as characters, folklore, and illustrations typical of the region. This design aims to increase the attractiveness and relevance of the book for children, so that it can motivate them in reading activities. At the Develop stage, the BCAC prototype that has been designed is then developed and evaluated through validity and practicality tests by experts and early childhood education practitioners. The results of the material expert validation gave a score of 41 (81%), the linguist gave a score of 48 (96%) while the media expert gave a score of 45 (90%) indicating that the BCAC was very feasible in terms of the suitability of the material to the curriculum and the quality of the illustrations. In addition, after a limited trial, BCAC was also rated as very practical by 2 practitioners with an average score of 41.5 83%. in the aspect of suitability for the development of early childhood reading literacy, as well as increasing children's interest in reading literacy by 34,8 (87%), in the initial observation the score was 26,1 (65,25%). Thus, BCAC is feasible and practical to use as a medium for learning reading literacy in early childhood. The development of BCAC not only improves children's reading literacy skills, but also introduces and instils local cultural values from an early age. It is hoped that BCAC can be an effective alternative learning media in improving early childhood reading literacy in Cirebon and surrounding areas.